2019
DOI: 10.18805/ijare.a-5321
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Farm Productivity in Flood Prone area: A Study in Dhemaji District of Assam

Abstract: Floods have threatened the agricultural productivity in Assam every year. Quality of soil, which is one of the important factors, that determines the production and income of farm, has been damaged by flood. Various study and secondary data reveal that deposition of sand due to flood has negative impact on farm productivity. This paper tries to investigate the impact of flood induced sand deposition and other factors on farm productivity in Dhemaji district, one of the mostly flood effected area of Assam. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Possible explanation of such result implies that an expansion in area affected by flood causes greater damage towards cultivation of crop thereby lowering the output level. Similar findings being arrived in the works of Younus (2014); Huang et al (2015); and Das and Bora (2020). The estimated coefficient of consumption of fertiliser in cultivation of crops like paddy, jowar, ragi, barley and total cereals seen to be statistically significant with positive elasticity.…”
Section: Resultssupporting
confidence: 83%
“…Possible explanation of such result implies that an expansion in area affected by flood causes greater damage towards cultivation of crop thereby lowering the output level. Similar findings being arrived in the works of Younus (2014); Huang et al (2015); and Das and Bora (2020). The estimated coefficient of consumption of fertiliser in cultivation of crops like paddy, jowar, ragi, barley and total cereals seen to be statistically significant with positive elasticity.…”
Section: Resultssupporting
confidence: 83%
“…For example, a study conducted in the low‐lying haor region showed that sedimentation had a negative impact on the cultivation of boro rice, the main cereal crop, and on the soil moisture and water holding capacity in the haor region (Chakraborty et al., 2021). Siltation has been reported as the primary cause of decreased cultivated land area and crop production in the neighboring countries of India and Nepal (Das, 2012; Kafle et al., 2017). The loss of water resources has sometimes resulted in the population having to drink contaminated water, thereby increasing various waterborne diseases (Buragohain & Bhuyan, 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The hill region is prone to landslides, especially during the rainy season, and during the monsoon season, very heavy rains transport gravel, sand and silt from the upstream areas and deposit them both on the fans and in the floodplain regions further downstream in the haor. The soils on the alluvial fans are generally poorly to incompletely drained, brown, very mottled, loamy sand to clay loam, poorly textured and with a strong to extreme reaction to acid (Das, 2012; IUCN, 2015).…”
Section: Conceptual Frameworkmentioning
confidence: 99%